2019
DOI: 10.3390/ijms20081891
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Metal Nanoclusters for Aggregation-Induced Emission

Abstract: Aggregation-induced emission (AIE) is an intriguing strategy to enhance the luminescence of metal nanoclusters (NCs). However, the morphologies of aggregated NCs are often irregular and inhomogeneous, leading to instability and poor color purity of the aggregations, which greatly limit their further potential in optical applications. Inspired by self-assembly techniques, manipulating metal NCs into well-defined architectures has achieved success. The self-assembled metal NCs often exhibit enhancing emission st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…In addition to organic probes, some nanoparticles and metal nanoclusters also show AIE behavior [84], and some of them have been used for Zn 2+ sensing with the merits of simple preparation, broad excitation range and high photostability [85,86]. For instance, copper nanoclusters (Cu NCs) are frequently used for fluorescence analysis with AIE activity [87,88].…”
Section: Zn 2+mentioning
confidence: 99%
“…In addition to organic probes, some nanoparticles and metal nanoclusters also show AIE behavior [84], and some of them have been used for Zn 2+ sensing with the merits of simple preparation, broad excitation range and high photostability [85,86]. For instance, copper nanoclusters (Cu NCs) are frequently used for fluorescence analysis with AIE activity [87,88].…”
Section: Zn 2+mentioning
confidence: 99%
“…Compared with gold and silver nanoclusters, copper nanoclusters (CuNC) have the advantages of low cost and environmental protection, which are regarded as one of the most promising MNC [3,4]. Since the sulfhydryl group of glutathione has good reducibility and strong chelation with copper ions, it is often used as a template and reducing agent for the synthesis of CuNC [5,6], even though it has a disadvantage of low quantum yield and easy oxidative denaturation in an aqueous solution [7]. Since CuNC triggered by Al 3+ can greatly increase the fluorescence intensity and stability of CuNC [8,9], several fluorescence probes based on the AIE performance of Al 3+ -triggered CuNC have been developed to detect β-galactosidase, creatinine, alkaline phosphatase, and urea, respectively [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that a much greater variety of nanoparticle assemblies could be produced by cells along the "bottom-up" approach (Zhang et al, 2011;Woehl et al, 2014;Sánchez-López et al, 2020) (Figure 1). Observations clearly show that nanocrystals can nucleate from an aqueous solution via a threestep mechanism: spinodal decomposition, clusterization, and nanocrystallization (Luo et al, 2017;Tan et al, 2017;Xie et al, 2017;Liao et al, 2019;Mikhailov and Mikhailova, 2019;Wang et al, 2019). The amorphous clusters of zero-valent atoms (up to 1-2 nm) are direct precursors of the bigger crystalline nanoparticles (Malis et al, 2011;Wan et al, 2013;Loh et al, 2017;Singh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in generated biogenic nanoparticles depend on the physiology of microorganisms as well as on the medium composition and conditions at their formation (Narayanan and Sakthivel, 2010;Zhang et al, 2011;Wang et al, 2012;Sorokin et al, 2013;Wu et al, 2013;Tyupa et al, 2016;Muller, 2018;Siddiqi et al, 2018). However, only metabolically active cells can rapidly (in minutes) generate metal nanoparticles from metal ions of the added salt due to their ability to constantly "efflux" electrons and electron donors into the medium (Zhou et al, 2013;Skladnev et al, 2017a;Wang et al, 2019). Inactive cells or cells with destroyed and non-active biostructures have a much weaker ability to reduce cations and form only the amorphous nanoclusters (up to 1-2 nm) as precursors of nanoparticles (Woehl et al, 2014;Liao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%